Black hole with confining electric potential in scalar-tensor description of regularized 4-dimensional Einstein-Gauss-Bonnet gravity - Övgün, Ali (Elsevier, 2021)
In this paper, we analytically present an exact confining charged black hole solution to the scalar-tensor description of regularized 4-dimensional Einstein-Gauss-Bonnet gravity (4DEGBG) coupled to non-linear gauge theory containing root-F-2 term. Part of the importance of using a non-trivial 4D theory of Gauss-Bonnet gravity is that it is proven the absence of the Ostrogradsky instability was formulated in Glavan and Lin (2020) [26] and then regularized 4DEGBG theory was obtained in Hennigar et al. (2020) [45] and Fernandes et al. (2020) [49] as well as this theory gains many attentions because of its important finding for black hole physics. We therefore also study some properties of this solution such as temperature, specific heat, shadowand quasinormal modes. Our results here show that a confining charge f gives a significant contribution to the shadow of the black hole as well as quasinormal modes frequencies. (C) 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/). Funded by SCOAP3.
Keywords: Black hole; Exact solutions; Gauss-Bonnet gravity; QCD-inspired confining potential; Shadow